PERTANGGUNGJAWABAN PIDANA MASKAPAI PENERBANGAN DALAM HAL TERJADINYA KECELAKAAN PESAWAT UDARA - Carmenia Yudithio, Theresia; Purwanti, Ni Putu (Kertha Wicara : Journal Ilmu Hukum, 2014)
The title of this paper is “Airlines Criminal Liability In Aircraft Accident". Commercial air transport is currently experiencing very rapid progress, it can be seen from the many airline companies that provide air transportation services are cheap and convenient for the passangers. Sometimes, problems arise, such as aircraft accidents. It can not be separated from the role that airlines sometimes more concerned with profits than the safety of passengers only user services. Thus the necessary legal framework in order to provide legal protection for air travelers and strict criminal penalties for violating the airline.
Keywords: Criminal Liability, Airlines, Aircraft Accident